Learning through online discussion: a framework evidenced in learners' interactions - Yvonne C. Bain (Association for Learning Technology, 2011)
Online learning, often supported through online discussion, is not only a popular means of supporting off-campus learners, but increasingly has a place within campus-based learning courses. Laurillard and others suggest that there are assumptions being made about learning through online discussion that have yet to be fully tested, and therefore there is a need to examine this area further. Tutors and learners may benefit from having a greater insight and understanding of how engaging in asynchronous online discussion presents opportunities for learning on an individual and a collective basis. This research study focused on learners' engagement with online discussion and their perceptions of how engaging in online discussion impacts on learning. This paper revisits learning through online discussion and proposes a framework, which emerges from the analysis of learners' experiences. A grounded theory approach was used in the collection and analysis of six learner case studies within a higher education setting, exploring learners' interactions in online discussion, and their perceptions of learning through online discussion. Insights into the learners' interactions were provided by the learners themselves through semi-structured interviews. The grounded approach to the analysis of the interviews enabled the learners' voices to be heard in terms of what they thought about learning through online discussion. The insight enabled through the depth of description from the learners and the examination of the online interactions led to the development of a framework for learning through online discussion. The framework raises the importance of articulation as a key process in learning whilst highlighting the opportunities for collaborative informed thinking by engaging with the ideas of others. The focus given to the learning process through the framework will be of interest to tutors and learners who use online asynchronous discussion environments for learning.